2003
DOI: 10.1034/j.1600-051x.2003.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic dental scaler: associated hazards

Abstract: This review outlines some of the research conducted into these areas of associated hazard in order to assess their significance in the clinical situation, and discusses ideas for future research. Suggestions of recommendations are given, which have been previously investigated for their aid in reducing possible hazards, to ensure the safe working of ultrasonic scalers in the dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 62 publications
0
82
0
1
Order By: Relevance
“…During medical transplant or other surgeries, health professionals might face the risk of inhaling airborne biological agents aerosolized from the patient's blood. Trenter and Walmsley (2003) have indicated that use of ultrasonic dental scaler during the dental operation could release aerosols that may contain dangerous bacteria. A recent study indicated that there was about 23% possibility of influenza virus infections in people wearing surgical and N95 respiratory masks (Loeb et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During medical transplant or other surgeries, health professionals might face the risk of inhaling airborne biological agents aerosolized from the patient's blood. Trenter and Walmsley (2003) have indicated that use of ultrasonic dental scaler during the dental operation could release aerosols that may contain dangerous bacteria. A recent study indicated that there was about 23% possibility of influenza virus infections in people wearing surgical and N95 respiratory masks (Loeb et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The topic continues to produce anecdotal stories from patients and operators [120,121]. The review by Trenter & Walmsley [122] is recommended.…”
Section: Exposuresmentioning
confidence: 99%
“…[9][10][11][12][13][14] As a result, statements cautioning dentists to avoid the use of ultrasonic scalers and other electrical dental devices with patients who have CIEDs have appeared in the literature. 6,[15][16][17] However, clinical data are limited. Published studies to date have included a low number of patients and case reports that have provided conflicting results.…”
mentioning
confidence: 99%